2017
DOI: 10.1096/fj.201700657r
|View full text |Cite
|
Sign up to set email alerts
|

Positional stable isotope tracer analysis reveals carbon routes during ammonia metabolism of Aedes aegypti mosquitoes

Abstract: In females, the ammonia released during blood meal digestion is partially metabolized to facilitate the disposal of excess nitrogen. In this study, we used low- and high-resolution liquid chromatography-mass spectrometry (LC/MS) techniques to investigate the role of glucose during ammonia detoxification. Mosquitoes were fed a blood meal supplemented with [1,2-C]glucose, and downstream metabolites were measured for 24 h. Quantification of [C] amino acids in the entire mosquito body was conducted without sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Fatty acyls can be acquired from the midgut digestion and absorption of a blood meal or can be de novo synthesized from central carbon metabolism precursors [ 27 , 52 ]. Fatty acids that are covalently linked to coenzyme A, fatty acyl-CoAs, can be incorporated into complex lipids such as GPs, SPs and GLs that have structural roles in membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Fatty acyls can be acquired from the midgut digestion and absorption of a blood meal or can be de novo synthesized from central carbon metabolism precursors [ 27 , 52 ]. Fatty acids that are covalently linked to coenzyme A, fatty acyl-CoAs, can be incorporated into complex lipids such as GPs, SPs and GLs that have structural roles in membranes.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that feeding on sugars increases survivorship in A. aegypti mosquitoes (Briegel et al, 2001; Foster, 1995). Carbohydrates are also required to support blood meal digestion, reproduction (Hou et al, 2015; Zhou et al, 2004), ammonia detoxification, and disposal of excess nitrogen in blood-fed A. aegypti females (Horvath et al, 2018), highlighting the importance of sugar metabolism in these insects. In this report, we demonstrate that the recombinant AaPK1 is allosterically regulated by specific sugars and amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…In this cycle, proline serves as a shuttle to move acetyl units between fat body and flight muscles. The pyruvate generated from different reactions, including decarboxylation of malate (Scaraffia and Wells, 2003) or as a product of PK can be utilized as a substrate of alanine aminotransferase, an enzyme involved in amino acid and ammonia metabolism in A. aegypti (Horvath et al, 2018; Isoe et al, 2017; Mazzalupo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The small amount of urea in the excreta is interesting in light of the recent finding that A. aegypti mosquitoes produce urea via an uricoltyic pathway (i.e., they metabolize uric acid via allantoin and allantoic acid to urea), rather than through the more common hydrolysis of arginine (Scaraffia et al, 2008;Horvath et al, 2018). While we did not investigate the mechanism by which urea is produced in E. vuilleti, the fact that both insects share a similar N-rich food (host circulatory fluid), suggests that a similar uricolytic pathway may be present in E. vuilleti, especially as a few samples showed relatively high levels of urea and low amounts of uric acid.…”
Section: Nature Of N Waste Compounds and Pathways For Excretionmentioning
confidence: 99%
“…The presence of small amounts of urea in excreta of terrestrial insects is interesting. In most cases, it is thought to result from the hydrolysis of arginine, but a recent study on the mosquito Aedes aegypti demonstrated that it was formed from uric acid through a functional amphibian-like uricolytic pathway; i.e., via allantoic acid (Scaraffia et al, 2008;Horvath et al, 2018).…”
Section: Introductionmentioning
confidence: 99%